2016
DOI: 10.1149/2.0241607jss
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High Performance Selective Solar Absorber with the Structure of SiO2-TiO2-TiNxOy-Cu

Abstract: Using TiN x O y thin film as the absorbing layer, a spectrally selective solar absorber (SSA) with the structure of SiO 2 -TiO 2 -TiN x O y -Cu has been designed; and the SSA performance has been evaluated by both calculation and experiment. The TiN x O y layer is fabricated by RF magnetron sputtering of a pure TiN target with Ar and N 2 gases. The introduction of oxygen in the TiN x O y is realized by using the residual oxygen in the deposition chamber. It is found that the N 2 flow rate has a large effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Different types of SSA, such as metal-dielectric composite, multilayer absorbers and semiconductor-metal tandems have been developed due to their higher thermal absorbance, higher thermal stability and low IR emittance [3][4][5][6]. In recent years, many types of selective solar absorber coatings for mid-to-high-temperature applications were studied, but only a few of them have been successfully commercialized.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different types of SSA, such as metal-dielectric composite, multilayer absorbers and semiconductor-metal tandems have been developed due to their higher thermal absorbance, higher thermal stability and low IR emittance [3][4][5][6]. In recent years, many types of selective solar absorber coatings for mid-to-high-temperature applications were studied, but only a few of them have been successfully commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers deposited TiN x O y using reactive magnetron sputtering and by changing the (N/O) ratio, with different types of AR layers such as TiO 2 /Si N 4 /SiO 2 and TiO 2 /SiO 2 to obtain efficient SSA [3,4,8]. Chen et al [4] found that the behavior of TiN x O y films was changed from metallic to dielectric behavior by increasing the oxygen content.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO x N y have also been investigated as selective solar absorber materials [31,32]. However, the spectral selectivity was achieved by using multi-layer structures and antireflection layers which requires several steps [33][34][35]. In addition, all the reported TiO x N y solar absorber materials have been prepared by using sputtering technique.…”
Section: Introductionmentioning
confidence: 99%